The Effects of e-WOM and Green Product Innovation on Consumer Purchase Decisions through Social Media Marketing on Beauty Products in Sociolla - Siti Asriah Immawati; Apriliani Anggi (Telaah Bisnis, 2022)
The study aims to analyze the determinant of electronic word of mouth and green product innovation on purchasing decisions through Social Media Marketing for beauty products at Sociolla. This research is quantitative, with a sample of 96 people. The non-probability sampling technique used is the accidental sampling technique. Primary data collection was obtained by distributing questionnaires. Data processing uses smart PLS and data analysis used in this study includes descriptive statistical analysis, instrument testing, classical assumption testing, regression analysis, hypothesis testing, and coefficient of determination testing. The results of the study show that partially and simultaneously social media marketing, electronic word of mouth, and green products affect purchasing decisions. The findings of this study are expected to provide fundamental data for strategy development related to social media marketing of beauty products. In addition, this study has implications for suggestions to increase the use of e-wom and green product innovation through social media marketing.